The uses of variety : modern Americanism and the quest for national distinctiveness - Bramen, Carrie Tirado, 1964- (Harvard University Press, 2000)
"Carrie Tirado Bramen pursues the idea of variety through the works of a wide range of regional and cosmopolitan writers, journalists, theologians, and politicians who rewrote the narrative of American exceptionalism through a celebration of variety. Exploring cultural and institutional spheres ranging from intra-urban walking tours in popular magazines to the 1893 World's Parliament of Religions in Chicago, she shows how the rhetoric of variety became naturalized and nationalized as quintessentially American and inherently democratic. By focusing on the uses of the term in the work of William James, Anna Julia Cooper, W.E.B